Combined pulsed laser deposition and non-contact atomic force microscopy system for studies of insulator metal oxide thin films - Katsube, Daiki; Yamashita, Hayato; Abo, Satoshi; Abe, Masayuki (Beilstein Journal of Nanotechnology, 2018)
We have designed and developed a combined system of pulsed laser deposition (PLD) and non-contact atomic force microscopy (NC-AFM) for observations of insulator metal oxide surfaces. With this system, the long-period iterations of sputtering and annealing used in conventional methods for preparing a metal oxide film surface are not required. The performance of the combined system is demonstrated for the preparation and high-resolution NC-AFM imaging of atomically flat thin films of anatase TiO2(001) and LaAlO3(100).
Keywords: atomic resolution; frequency modulation atomic force microscopy; insulator thin film; pulsed laser deposition

The Surface Science of Metal Oxides - Henrich, V.; Cox, P. (Cambridge University Press, 1994)

(untitled) - Ohta, H.; Orita, M.; Hirano, M.; Tanji, H.; Kawazoe, H.; Hosono, H. (Appl. Phys. Lett., 2000)

(untitled) - Ohta, H.; Orita, M.; Hirano, M.; Hosono, H. (J. Appl. Phys., 2002)

(untitled) - Ohtomo, A.; Hwang, H. Y. (Nature, 2004)

(untitled) - Gozar, A.; Logvenov, G.; Kourkoutis, L. F.; Bollinger, A. T.; Giannuzzi, L. A.; Muller, D. A.; Bozovic, I. (Nature, 2008)

(untitled) - Matsumoto, Y.; Murakami, M.; Shono, T.; Hasegawa, T.; Fukumura, T.; Kawasaki, M.; Ahmet, P.; Chikyow, T.; Koshihara, S.; Koinuma, H. (Science, 2001)

(untitled) - Furubayashi, Y.; Hitosugi, T.; Yamamoto, Y.; Inaba, K.; Kinoda, G.; Hirose, Y.; Shimada, T.; Hasegawa, T. (Appl. Phys. Lett., 2005)

(untitled) - Erdman, N.; Poeppelmeier, K. R.; Asta, M.; Warschkow, O.; Ellis, D. E.; Marks, L. D. (Nature, 2002)

(untitled) - Lanier, C. H.; Rondinelli, J. M.; Deng, B.; Kilaas, R.; Poeppelmeier, K. R.; Marks, L. D. (Phys. Rev. Lett., 2007)

(untitled) - Erdman, N.; Warschkow, O.; Asta, M.; Poeppelmeier, K. R.; Ellis, D. E.; Marks, L. D. (J. Am. Chem. Soc., 2003)

(untitled) - Yuan, W.; Wu, H.; Li, H.; Dai, Z.; Zhang, Z.; Sun, C.; Wang, Y. (Chem. Mater., 2017)

(untitled) - Sugiyama, I.; Shibata, N.; Wang, Z.; Kobayashi, S.; Yamamoto, K.; Ikuhara, Y. (Nat. Nanotechnol., 2013)

(untitled) - Ohsawa, T.; Saito, M.; Hamada, I.; Shimizu, R.; Iwaya, K.; Shiraki, S.; Wang, Z.; Ikuhara, Y.; Hitosugi, T. (ACS Nano, 2015)

(untitled) - Koguchi, K.; Matsumoto, T.; Kawai, T. (Science, 1995)

(untitled) - Morales, E. H.; Diebold, U. (Appl. Phys. Lett., 2009)

(untitled) - Tao, J.; Luttrell, T.; Batzill, M. (Nat. Chem., 2011)

(untitled) - Gong, X.; Selloni, A.; Batzill, M.; Diebold, U. (Nat. Mater., 2006)

(untitled) - Ma, J. X.; Gillaspie, D. T.; Plummer, E. W.; Shen, J. (Phys. Rev. Lett., 2005)

(untitled) - Kubo, T.; Nozoye, H. (Phys. Rev. Lett., 2001)

(untitled) - Kresse, G.; Schmid, M.; Napetschnig, E.; Shishkin, M.; Köhler, L.; Varga, P. (Science, 2005)

(untitled) - Schintke, S.; Messerli, S.; Pivetta, M.; Patthey, F.; Libioulle, L.; Stengel, M.; De Vita, A.; Schneider, W.-D. (Phys. Rev. Lett., 2001)

(untitled) - Glöckler, K.; Sokolowski, M.; Soukopp, A.; Umbach, E. (Phys. Rev. B, 1996)

(untitled) - Tanner, R. E.; Sasahara, A.; Liang, Y.; Altman, E. I.; Onishi, H. (J. Phys. Chem. B, 2002)

(untitled) - Crommie, M. F.; Lutz, C. P.; Eigler, D. M. (Nature, 1993)

(untitled) - Hasegawa, Y.; Avouris, P. (Phys. Rev. Lett., 1993)

(untitled) - Gerhold, S.; Wang, Z.; Schmid, M.; Diebold, U. (Surf. Sci., 2014)

(untitled) - Shimizu, R.; Iwaya, K.; Ohsawa, T.; Shiraki, S.; Hasegawa, T.; Hashizume, T.; Hitosugi, T. (ACS Nano, 2011)

(untitled) - Ohsawa, T.; Shimizu, R.; Iwaya, K.; Hitosugi, T. (ACS Nano, 2014)

(untitled) - Sawada, D.; Sugimoto, Y.; Morita, K.; Abe, M.; Morita, S. (Appl. Phys. Lett., 2009)

(untitled) - Stetsovych, O.; Todorović, M.; Shimizu, T. K.; Moreno, C.; Ryan, J. W.; Pérez León, C.; Sagisaka, K.; Palomares, E.; Matolín, V.; Fujita, D.; Perez, R.; Custance, O. (Nat. Commun., 2015)

(untitled) - Torbrügge, S.; Ostendorf, F.; Reichling, M. (J. Phys. Chem. C, 2009)

(untitled) - Torbrügge, S.; Reichling, M.; Ishiyama, A.; Morita, S.; Custance, O. (Phys. Rev. Lett., 2007)

(untitled) - Fukui, K.; Onishi, H.; Iwasawa, Y. (Phys. Rev. Lett., 1997)

(untitled) - Canova, F. F.; Foster, A. S.; Rasmussen, M. K.; Meinander, K.; Besenbacher, F.; Lauritsen, J. V. (Nanotechnology, 2012)

(untitled) - Barth, C.; Reichling, M. (Nature, 2001)

(untitled) - Suzuki, S.; Ohminami, Y.; Tsutsumi, T.; Shoaib, M. M.; Ichikawa, M.; Asakura, K. (Chem. Lett., 2003)

(untitled) - Katsube, D.; Takase, Y.; Yamashita, H.; Abo, S.; Wakaya, F.; Abe, M. (Mater. Trans., 2015)

(untitled) - Bettac, A.; Koeble, J.; Winkler, K.; Uder, B.; Maier, M.; Feltz, A. (Nanotechnology, 2009)

(untitled) - Hoffmann, R.; Lantz, M. A.; Hug, H. J.; van Schendel, P. J. A.; Kappenberger, P.; Martin, S.; Baratoff, A.; Güntherodt, H.-J. (Appl. Surf. Sci., 2002)

(untitled) - Heyde, M.; Sterrer, M.; Rust, H.-P.; Freund, H.-J. (Appl. Phys. Lett., 2005)

(untitled) - Abe, M.; Sugimoto, Y.; Morita, S. (Nanotechnology, 2005)

(untitled) - Yurtsever, A.; Sugimoto, Y.; Abe, M.; Morita, S. (Nanotechnology, 2010)

(untitled) - Yokoyama, K.; Ochi, T.; Uchihashi, T.; Ashino, M.; Sugawara, Y.; Suehira, N.; Morita, S. (Rev. Sci. Instrum., 2000)

(untitled) - Sugimoto, Y.; Abe, M.; Hirayama, S.; Oyabu, N.; Custance, Ó.; Morita, S. (Nat. Mater., 2005)

(untitled) - Sugimoto, Y.; Pou, P.; Abe, M.; Jelinek, P.; Pérez, R.; Morita, S.; Custance, O. (Nature, 2007)

(untitled) - Abe, M.; Sugimoto, Y.; Namikawa, T.; Morita, K.; Oyabu, N.; Morita, S. (Appl. Phys. Lett., 2007)

(untitled) - Sugimoto, Y.; Pou, P.; Custance, O.; Jelinek, P.; Abe, M.; Perez, R.; Morita, S. (Science, 2008)

(untitled) - Sugimoto, Y.; Abe, M.; Yoshimoto, K.; Custance, O.; Yi, I.; Morita, S. (Appl. Surf. Sci., 2005)

(untitled) - Okano, M.; Kajimura, K.; Wakiyama, S.; Sakai, F.; Mizutani, W.; Ono, M. (J. Vac. Sci. Technol., A, 1987)

(untitled) - Rugar, D.; Mamin, H. J.; Guethner, P. (Appl. Phys. Lett., 1989)

(untitled) - Albrecht, T. R.; Grütter, P.; Horne, D.; Rugar, D. (J. Appl. Phys., 1991)

(untitled) - Kurita, D.; Ohta, S.; Sugiura, K.; Ohta, H.; Koumoto, K. (J. Appl. Phys., 2006)

(untitled) - Katayama, M.; Ikesaka, S.; Kuwano, J.; Koinuma, H.; Matsumoto, Y. (Appl. Phys. Lett., 2008)

(untitled) - Chambers, S. A.; Wang, C. M.; Thevuthasan, S.; Droubay, T.; McCready, D. E.; Lea, A. S.; Shutthanandan, V.; Windisch, C. F., Jr (Thin Solid Films, 2002)

(untitled) - Shao, R.; Wang, C.; McCready, D. E.; Droubay, T. C.; Chambers, S. A. (Surf. Sci., 2007)

(untitled) - Horcas, I.; Fernández, R.; Gómez-Rodríguez, J. M.; Colchero, J.; Gómez-Herrero, J.; Baro, A. M. (Rev. Sci. Instrum., 2007)

(untitled) - Setvín, M.; Daniel, B.; Mansfeldova, V.; Kavan, L.; Scheiber, P.; Fidler, M.; Schmid, M.; Diebold, U. (Surf. Sci., 2014)

(untitled) - Gariglio, S.; Reyren, N.; Caviglia, A. D.; Triscone, J.-M. (J. Phys.: Condens. Matter, 2009)

(untitled) - Tebano, A.; Fabbri, E.; Pergolesi, D.; Balestrino, G.; Traversa, E. (ACS Nano, 2012)

(untitled) - Shalom, M. B.; Sachs, M.; Rakhmilevitch, D.; Palevski, A.; Dagan, Y. (Phys. Rev. Lett., 2010)